Exploring Potential Factors in Green and Sustainable Software Product - Komeil Raisian; Jamaiah Yahaya; Aziz Deraman (Society of Visual Informatics, 2018)
software engineering is a principle role of our activity in social and economic life. Software engineers are starting to comprehend the significance of designing sustainability regarding software processes. The field of sustainable and green software and green software engineering is still young. Thus, in modern society, researches effort is mainly focused on green and sustainable software engineering itself.Â In other words, the aim of this study at hand aims an in-depth understanding of the related potential factors for the purpose of improving the recently reluctant trend of sustainability dimension in green software based on life cycle of green software product process. To reach this purpose, this study is reviewed latest research and used conceptual model. A conceptual model is rendered demonstrating the consolidated life cycles of sustainable product and principle sustainable measurement dimensions, for example, energy or information efficiency, low cost, Resource efficiency, Waste reduction, Equality support and human health.